The Neuromodulatory Effect of Antipruritic Treatment of Chronic Prurigo - Claudia Zeidler; Manuel Pereira; Sonja Ständer (Adis, Springer Healthcare, 2019)
Abstract Chronic prurigo is an extremely severe pruritic skin disease which presents with multiple, hyperkeratotic and erosive papules, nodules and/or plaques. Patients with this high-burden disease require effective therapies, but effective treatments with regulatory agency approval are currently lacking. Deeper understanding of the pathophysiology suggests that hypersensitive nerves play an important role in the development of chronic prurigo. Accordingly, a treatment with neuroactive substances which modulate hypersensitivity seems promising. Here, we review antipruritic therapies with a neuromodulative effect. Current treatment options, such as topical capsaicin or opioid-receptor modulators, and also novel and future treatment regimens, such as, for example, interleukin-31 antibodies and neurokinin-1 receptor antagonists, are discussed.